Barriers, Attitudes, Confidence and Knowledge of Mental Health and Psychosocial Humanitarian Staff in Cox’s Bazar in Responding to Suicide Risk - Lauren Fischer; Ariel Zarate; Kamruzzaman Mozumder; Mohamed Elshazly; Simon Rosenbaum (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas, 2021)
Although suicide is a significant global health priority, it is underexamined in humanitarian crises. Over 850,000 Rohingya reside as refugees in Cox’s Bazar, Bangladesh; suicide risk may be high in this community by some indicators, but little is definitively known. Even less is known about humanitarian workers’ capacity to recognise and respond to suicide risk in affected communities. Participants were mental health and psychosocial support (30%), protection (31%), gender-based violence (17%) and others (22%) multisectoral humanitarian staff having weekly face-to-face contact with Rohingya refugees as part of their professional duties. We assessed barriers, attitudes, competence and knowledge regarding suicide-risk response. The survey was disseminated over 3 weeks in June 2020, engaging 181 respondents from multiple sectors of the coordinated response. Respondents who had prior training scored higher on the overall scale compared to those without (P ≤ 0.001), and there was a significant impact of prior training on attitudes (P = 0.005), confidence (P = 0.002) and knowledge (P ≤ 0.001). Humanitarian staff from multiple sectors reported low confidence or readiness to respond to suicide risk in the field. Training on suicide identification, intervention and response for such staff and related community gatekeepers is an urgent need in the Rohingya refugee response.